Octamer 4 expression and lymph node metastasis in ductal carcinoma of breast: Are they associated? - Sangita A Vanik; Shakti Kumar Yadav; Aarzoo Jahan; Sonam Kumar Pruthi; Namrata Sarin; Ratna Chopra; Sompal Singh (Indian Journal of Medical and Paediatric Oncology)
Purpose: Octamer 4 (Oct-4) is a transcription factor which is required for the self-renewal and pluripotency of embryonic stem cells and germ cells. In this study, we tried to examine the association of expression of Oct-4 with lymph node metastasis in ductal carcinoma of the breast. Methods: The study was conducted on a total of 45 cases of invasive ductal carcinoma of breast, no special type. Oct-4 expression was studied on paraffin-embedded sections by immunohistochemistry. Results: Oct-4 expression was seen in 22.2% of cases. No statistically significant association was found between the expression of Oct-4 and histological type, tumor size, histological grade, and lymph node metastasis. Of Oct-4 positive tumor, 80% of cases showed lymph node metastasis, as compared to 62.85% without Oct-4 expression. However, the association was statistically insignificant. Conclusion: Oct-4 expression can be a promising biomarker of carcinogenesis, metastatic potential, and prognosis of carcinoma breast. However, the study with larger sample size is needed to establish the clinicopathological potential of this biomarker.